Home nodes, criminogenic places, and parolee failure: testing an environmental model of offender risk - Miller, Joel (Crime & delinquency, 2016)
This article examines whether potentially criminogenic places (including bars, liquor stores, restaurants, public transport hubs, drug markets, and more), located within a 1,240-feet radius of parolees’ residences (the home “node”), predict their rearrest or revocation. Taking these features into account, in addition to individual traits and behaviors, might pave the way for more accurate risk assessment that could help make supervision sensitive to place-based risks. However, multivariate survival analysis of 1,632 parolees released to Newark during July 2007 to June 2009 found little evidence that these factors increased the risk of failure. Successful operationalization of environmental risk will probably need to incorporate more detailed measures of parolees’ routine activities, including the settings and paths they frequent beyond their home environment.